2010
DOI: 10.1029/2009jc006037
|View full text |Cite
|
Sign up to set email alerts
|

The role of the critical angle in brightness reversals on sunglint images of the sea surface

Abstract: [1] A wide variety of oceanic and atmospheric phenomena are often observed in and around the sunglint region on optical images of the sea surface. The appearance of these phenomena depends strongly on the viewing geometry with areas on the sea surface that are rougher (or smoother) than the background appearing as either brighter or darker than the background depending on their position relative to the specular point. To understand these sea surface signature variations, this paper introduces the concept of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 25 publications
(50 reference statements)
6
79
0
Order By: Relevance
“…A wide variety of oceanic and atmospheric phenomena have been observed in and around the sun glint region on optical images of the sea surface (Jackson and Alpers 2010). A sun glint region is a region from which the satellite views the mirror-like reflection from the Sun.…”
Section: Satellite Sun Glint Imagesmentioning
confidence: 99%
See 3 more Smart Citations
“…A wide variety of oceanic and atmospheric phenomena have been observed in and around the sun glint region on optical images of the sea surface (Jackson and Alpers 2010). A sun glint region is a region from which the satellite views the mirror-like reflection from the Sun.…”
Section: Satellite Sun Glint Imagesmentioning
confidence: 99%
“…The sun glint region can be modelled well for a known satellite orbit at a specific date/ time (Jackson and Alpers 2010;Zhang and Wang 2010). It is calculated using the latitude/ longitude points, Sun and satellite sensor azimuth and zenith angles, and ocean surface winds.…”
Section: Satellite Sun Glint Imagesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the sun glitter geometry model, it has been found that the signature of sun glitter images depends strongly on the viewing angle. 19,23,24 He et al 25 discussed the brightness reversal of the Taiwan Banks submarine sand waves in sun glitter images from charge-coupled diodes onboard the HJ-1B satellite. Therefore, multiangle sun glitter images can present useful additional information compared with single angle images.…”
Section: Introductionmentioning
confidence: 99%